A new structure on the frons of male adults of the Asian rice spittlebug Callitettix versicolor (Hemiptera: Auchenorrhyncha: Cercopidae) - Liang, Ai-Ping (Zootaxa, 2020)
A new structure, here tentatively named the “frontal gland,” specifically found on frons of male adults of the Asian rice spittlebug, Callitettix versicolor (Fabricius, 1794) (Hemiptera: Auchenorrhyncha: Cercopidae), is reported. Adult C. versicolor is distinctly dimorphic in frons morphology. The frons in female adults, like that in most cercopid species, is normally swollen and nearly bulbose and is covered with short pilosity, while the frons in male adults is visibly different, with the lower 3/5 of the postclypeus and anteclypeus being centrally flat, bare and smooth on the surface. SEM observations revealed that the flat frons surface of the male adults is covered with numerous, very fine pores. In total, each frons has over 4500 pores on the central flat area, with an average density of 55.5 ± 1.50 pores per 100 µm2. The distance among the pores averages 10.63 ± 1.8 µm. Each pore unit is composed of a round, deep cavity in which one central conical process is set. The cavity is delimited by a cuticular rim and the opening of the cavity averages 2.89 ± 0.20 µm in diameter. The central, conical process has a sponge-like apex and measures 2.52–2.70 µm in diameter. In addition, one or two (two in most cases) extremely fine pits (0.42–0.56 µm in diameter) are located on the marginal cuticle rim surrounding the cavity and its central conical process. These cuticular, fine pits are located proximal to the pores, at a distance of 0.98–1.96 µm. These porous structures are not present on the frons in female adults. They are assumed to be an exocrine gland system and are possibly the male sex pheromone-releasing glands, as they are only present in male adults. Observations of mating behavior showed that it is likely that the secretions made by the frontal gland constitute short-range attractants and may fulfil aphrodisiac functions to stimulate mating. The species of Auchenorrhyncha were previously thought to communicate via acoustic signals, but the findings described here suggest that at least one Auchenorrhynchan species also uses chemicals for sexual communication.